Achieving Correct Axis and Good Depth in Gender Affirming Vaginoplasties by Penile-Perineoscrotal Flap Vaginoplasty - Gupta, Richie; Gupta, Rajat (Indian Journal of Plastic Surgery, 2022)
Objectives Vaginoplasty as a part of feminizing genitoplasty (FG) in transwomen helps alleviate gender dysphoria and improves mental health, sexual and psychosocial functioning, and quality of life in these individuals. Penile inversion technique (PSFV) remains the gold standard procedure for FG with least morbidity but has inherent limitations often resulting in inadequate depth and incorrect (posteroinferior) vaginal axis, precluding sexual intercourse.Material and Methods Over the past 27 years, the senior author has refined his technique considerably incorporating several modifications penile perineo-scrotal flap vaginoplasty (PPSFV) to overcome the limitations in PSFV. Most of these modifications were in place by March 2015. Out of 630 primary FGs, retrospective review of all PPSFV with minimum 6 months follow-up operated during the period March 2015 to July 2020 was done for intra and postoperative complications.Results There were 183 patients who underwent PPSFV during the study period. Average follow-up was 31 (6–62) months. There were no cases of injury to bladder, rectum, urethral stenosis, or neovaginal prolapse. Average operative time was 4 hours and eight (4.37%) patients required blood transfusion. The vaginal depth was 13 to 14 cm or more in 159 (86.88%), 10 to 12 cm in 17 (9.29%), and 7.5 to 9 cm in seven (3.82%) patients. Ten (5.46%) patients complained of intravaginal hair growth. Touch up procedures in the form of anterior commissure and labia plasty were required in 13 (7.10%) patients. All (100%) patients had good clitoral sensitivity and preserved posterosuperior vaginal axis. One-hundred thirty nine (75.96%) patients were able to have satisfactory penetrative sexual intercourse, while 39 (21.31%) had not attempted intercourse and five (2.73%) complained of poor sexual experience on account of inadequate vaginal dimensions.Conclusion PPSFV addresses the limitations in PSFV and results in good vaginal depth and posterosuperior axis, which facilitates penetrative sexual intercourse, at the same time, avoiding potential complications of procedures such as intestinal vaginoplasties.
Keywords: vaginoplasty; penile inversion vaginoplasty; feminizing genitoplasty; gender affirmation surgery; gender incongruence; gender dysphoria